SURFACING – TECHNOLOGIES AND LAYER PROPERTIES (A REVIEW) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The overview includes the basic methods for obtaining surface layers: arc surfacing - submerged arc surfacing (SAS), tungsten inert gas arc surfacing (TIGS), metal gas surfacing (MIG/MAG), plasma surfacing (PS); electron beam surfacing (EBS); laser surfacing (LS); electroless cladding (ELC); friction stir surfacing (FSS). Layers are applied on carbon steels, low alloyed steels, highly alloyed steels, aluminium alloys, titanium alloys or ductile cast iron substrates. The data on the additive materials used are provided and data on the hardness and wear resistance of the layers is given.